Pengaruh Pengalaman Praktik Kerja Lapangan (PKL) Dan Employability Skills Terhadap Kesiapan Kerja Siswa SMK Negeri 1 Banyudono - Arifah Nur Hayati; Patni Ninghardjanti; Susantiningrum Susantiningrum (Journal of Creative Student Research, 2024)
The purpose of this research was to determine: (1) the influence of practical field work experience on the work readiness of students at SMK Negeri 1 Banyudono, (2) the influence of employability skills on the work readiness of students at SMK Negeri 1 Banyudono, (3) the influence of practical field work experience and Employability skills on work readiness of students at SMK Negeri 1 Banyudono. This research is a type of research using quantitative methods. The research sample was class XII students at SMK Negeri 1 Banyudono obtained using a simple random sampling technique, and the sample obtained was 187 students. Data collection uses a questionnaire. The research results show that there is (1) a positive and significant influence between practical field work experience on work readiness with the regression line equation Ŷ = 4.982 + 0.285X1 with a coefficient of determination (R2) of 0.653 and an effective contribution of 18.4%, (2) a positive and significant influence between employability skills on work readiness with the regression line equation Ŷ = 4.982 + 0.672X2 with a coefficient of determination (R2) of 0.653 and an effective contribution of 47.59%, (3) a positive and significant influence between practical experience field work and employability skills on work readiness based on the regression line equation Ŷ = 4.982 + 0.285X1 + 0.672X2, with a coefficient of determination (R2) of 0.653 and the effective contribution given jointly is 65.7% while the remaining 34.3% explained by other variables that are not in this study.